Ortaġasyr da̋uìrìndegì christiandar men mu̇sylmandardyṇ ôzara a̋rekettesuìndegì dìni stereotipter - Satershinov, B. (Chabaršy. Dintanu serijasy, 2021)
The article reveals the problem of Christian-Islamic relations in the context of overcoming religious stereotypes. The authors believe that religious stereotypes have a negative impact on the dialogical culture of thinking and "inhibit" interfaith interaction. Religious stereotyping very often became a trigger in religious wars. The stereotypes that emerged from the religious sphere are historically stable; the dynamics of their change is associated with the modernization of society and social consciousness. Of course, stereotypes can also be positive when it comes to intercultural communication, where stereotypes seem to be the universal characteristics of a particular culture. In this article, the authors consider only religious stereotyping, which has a negative context associated with a false, irrelevant understanding and subjective interpretation of religious traditions and attitudes towards them that took place in history. The authors of the article believe that a person often resorts to stereotypes if he strives for "lightweight" versions of knowledge about particular subject. But for a person in need of deep knowledge, stereotypes act as "idols of knowledge" that F. Bacon called for deconstructing. Of particular negative significance are stereotypes that have appeared in the religious sphere, becoming very often an influential ideological force, turning into prejudices that affect interfaith relations. Religious stereotypes should not become a factor of separation, and stereotyping should be avoided in one of the most subtle spheres of human communication − spiritual and religious.